Peran Hakim Dalam Upaya Menurunkan Angka Dispensasi Nikah Di Kabupaten Bojonegoro (Studi Kasus Di Pengadilan Agama Bojonegoro Tahun 2022) - Jalil, Abdul; Umar, Mas; Azhar, Hanif (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
Early marriage is still a phenomenon in this country. Several sources say that the rate of early marriage is still high in Indonesia. One of the 2018 Supreme Court annual reports states that Religious Courts (PA) throughout Indonesia issued 13,251 marriage dispensations. According to the Ministry of PPPA (Ministry of Women's Empowerment and Child Protection, in 2021 there were 65 thousand cases recorded and in 2022 55 thousand applications for marriage dispensation were submitted. This is directly proportional to the application for marriage dispensation in 2022 in Bojonegoro Regency which was quite high with 532 application cases. When compared with other districts such as Gresik, Lamongan, Tuban, Nganjuk, and Ngawi, the number of cases of early marriage in Bojonegoro is quite high. The formulation of the problem in this research is 1. What do the judges think about solutions to prevent and reduce the level of marriage dispensation in Bojonegoro Regency 2. What are the factors causing the increase in marriage dispensations in the Bojonegoro Religious Courts in 2022? The type of research we use includes qualitative research. Meanwhile, the approach we use is a case study approach. The nature of this research is analytical descriptive, the data collection method. as follows: a) Observation Method, b) Interview Method, c) Documentation. While the author uses data analysis: 1). Data Reduction, 2). Data Display, 3). From the results of the research, the author found the following: 1. Factors causing the high level of marriage dispensation in Bojonegoro Regency are caused by several things, namely: a). Due to promiscuity, b). The bride and groom are getting along like husband and wife, c). The prospective bride is already pregnant, d). The bride-to-be has given birth, e). Permissive Community Culture, f). Local Officials Are Still Weak, g). The existence of a